2021
DOI: 10.3390/diagnostics11112059
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cardiac Sequelae in Patients Referred into a Diagnostic Post-COVID-19 Pathway: The Different Impacts on the Right and Left Ventricles

Abstract: Most patients who had COVID-19 are still symptomatic after many months post infection, but the long-term outcomes are not yet well defined. The aim of our prospective/retrospective study was to define the cardiac sequelae of COVID-19 infection. This monocentric cohort study included 160 consecutive patients who had been discharged from the ward or from the outpatient clinic after a diagnosis of COVID-19 and subsequently referred for a follow-up visit. Clinical features’ data about the acute phase along with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
1
16
1
Order By: Relevance
“…Demographics, co-morbidities, and acute organ dysfunction at admission were correlated with lower LVEF and higher BNP. Other studies found ventricular systolic dysfunction in Post-COVID-19 condition (23,24,31) and acute cardiac dysfunction was associated with readmission and late mortality (57). Surprisingly, we did not observe any associations of acute hospital course variables with subjective 3and 6-month outcomes (quality of life, shortness of breath or frailty).…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Demographics, co-morbidities, and acute organ dysfunction at admission were correlated with lower LVEF and higher BNP. Other studies found ventricular systolic dysfunction in Post-COVID-19 condition (23,24,31) and acute cardiac dysfunction was associated with readmission and late mortality (57). Surprisingly, we did not observe any associations of acute hospital course variables with subjective 3and 6-month outcomes (quality of life, shortness of breath or frailty).…”
Section: Discussioncontrasting
confidence: 92%
“…Prior studies show features of restrictive lung disease in Post-COVID-19 condition: decreased diffusing capacity (25) in 45 to 50% (16,17,25) and decreased lung volumes (26)(27)(28)(29). Objective cardiac dysfunction in Post-COVID-19 condition is less common: increased pulmonary artery pressures, left ventricular strain (30), and ventricular systolic dysfunction in 10(31)-15% (13,23,24,31). Renal dysfunction occurs in Post-COVID-19 condition (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of subclinical RV dysfunction in patients with COVID‐19 is important to discuss as reductions in RV strain are associated with greater mortality (Li et al, 2020 ). RV strain does appear to be a common finding during follow‐ups, even in patients with no history of cardiovascular or lung disease, and no presence of heart failure symptoms (Nuzzi et al, 2021 ), indicating that there is potential for silent cardiac (myocyte) damage and hemodynamic instability post‐COVID‐19 (Pelà et al, 2021 ).…”
Section: Cardiac Functionmentioning
confidence: 99%
“…In patients with persistent symptoms 5 months after initial SARS-CoV2 infection, 39% had echocardiographic findings of RV dilatation, 16% had findings of left ventricular (LV) diastolic dysfunction, and 10% had findings of LV systolic dysfunction [ 58 •]. Another prospective cohort study in low-risk patients with PCS 4 months post-infection found that 9% of patients had some systolic dysfunction on CMR with the incidence increasing as the severity of PCS increased [ 59 •].…”
Section: Heart Failure and Cardiomyopathiesmentioning
confidence: 99%